If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-2) + 2y = 8 Multiply 2 * -2 -4 + 2y = 8 Solving -4 + 2y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2y = 8 + 4 Combine like terms: -4 + 4 = 0 0 + 2y = 8 + 4 2y = 8 + 4 Combine like terms: 8 + 4 = 12 2y = 12 Divide each side by '2'. y = 6 Simplifying y = 6
| n^3+17n^2+72n=0 | | -2x+4=-12 | | 3-(1-6x)=2+4x | | 2(-5)+2y=8 | | 7n+14=-56 | | 2(3)+2y=8 | | 3y+5=5 | | 7x+26=136+2x | | 2x^4+4x=x^3+8x^2 | | 1-8x+5=11-3 | | -15+5x=-55 | | 2x(3+x)=0 | | 33+3b=-18 | | r^2=-14r-49 | | 14-5y=-21 | | 6-10x=46-17x | | 4n^2-52n+120=0 | | 3k^2+12k-79=7 | | -56-4y=-28 | | 1x=32 | | -12x^2+12=0 | | 8+3x=-24 | | 2+y=5 | | 9x-18=-27 | | 4x^3+12x=0 | | 22+x=4-8x | | 4=3t-2 | | 4r^2+32r=0 | | 194-2x=43x+24 | | 3x-6=-99 | | -0.4x+3=1 | | -21=x-12 |